2001
DOI: 10.1038/modpathol.3880286
|View full text |Cite
|
Sign up to set email alerts
|

Hamartin and Tuberin Expression in Human Tissues

Abstract: Tuberous sclerosis (TSC) is a bigenic autosomal dominant disease caused by mutations in one of two tumor-suppressor genes, TSC1 and TSC2, resulting in benign hamartomas and low grade neoplasms in multiple organs including brain, heart, kidney, and skin. We report the results of an immunohistochemical study of the expression of the TSC gene products, tuberin and hamartin, in multiple tissues obtained at autopsy from 12 non-TSC affected patients ranging in age from 20 weeks gestation to 8 years, and surgical spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 26 publications
(28 reference statements)
1
34
0
2
Order By: Relevance
“…This association has been demonstrated by immunohistochemical colocalization studies (58)(59)(60)(61)(62)(63) as well as by coimmunoprecipitation from subcellular fractions (64). In their elegant series of experiments, Nellist and colleagues (44) showed that hamartin and tuberin are binding partners that coelute from subcellular fractions in a complex with a molecular weight of 450 kD, larger than the combined molecular weights of hamartin and tuberin.…”
Section: Hamartin and Tuberin Physically Interactmentioning
confidence: 99%
“…This association has been demonstrated by immunohistochemical colocalization studies (58)(59)(60)(61)(62)(63) as well as by coimmunoprecipitation from subcellular fractions (64). In their elegant series of experiments, Nellist and colleagues (44) showed that hamartin and tuberin are binding partners that coelute from subcellular fractions in a complex with a molecular weight of 450 kD, larger than the combined molecular weights of hamartin and tuberin.…”
Section: Hamartin and Tuberin Physically Interactmentioning
confidence: 99%
“…2). 14,15 Most reports localise hamartin in the cytoplasm, although 1 of the studies explaining lack of TSC1/TSC2 complex activity in spite of the presence of wild-type proteins demonstrated nuclear localisation. 16 The protein is hydrophilic and has a single transmembrane domain at amino acids 127-144 and a predicted coiled-coil region at residues 719-998.…”
Section: Hamartinmentioning
confidence: 99%
“…Most 'second hits' are large deletions involving loss of surrounding loci and loss of heterozygosity (LOH) in TSC1 or TSC2, which have (Sancak et al 2005). However, the most common TSC-associated lesions are limited to relatively few organs including the brain, heart, kidney, lungs and skin, while the TSC gene products (hamartin and tuberin) are expressed in most tissues (Johnson et al 2001). Tuberin was present in abundance in control brains, but was lost from TSC tissues, such as cerebral cortices, cortical tubers and subependymal giant-cell astrocytomas (Mizuguchi et al 1996).…”
Section: Molecular Biology Of Tscmentioning
confidence: 99%